Analisis Implementasi Video Animasi Cerita untuk Meningkatkan Motivasi Belajar Siswa pada Pelajaran Bahasa Indonesia - Nurul Choirina; Banun Havifah Cahyo Khosiyono; Ana Fitrotun Nisa; Berliana Henu Cahyani (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
Motivation to learn is needed in order to get optimal learning results. Students with low motivation will be lazy and not interested in the learning process. This happened in the researcher's class. This research aims to analyze the implementation of animation story videos to increase student motivation in learning in class of fourth grade at SD Negeri 2 Sedayu in the 2024/2025 academic year in Bahasa Indonesia lessons. The method used by researchers in this research is a qualitative method. Observation and interviews are techniques used to collect data. The instruments used in this research were observation sheets and interview sheets. The data analysis technique used is descriptive qualitative. The subjects of this research were 14 students of fourth grade IV at SD Negeri 2 Sedayu for the 2024/2025 academic year, consisting of 10 male students and 4 female students. The results of this research show that students' learning motivation in Bahasa Indonesia lessons increases with the implementation of animated story videos. This can be seen based on the results of observations and responses to feelings in the interview results. It is hoped that the implementation of animation story videos can be applied to further Bahasa Indonesia lessons. Suggestions for further research are optimizing students' questioning skills through the implementation of animation story videos.